Curriculum and Material Development Using Content and Language Integrated Learning (CLIL) for Teaching Science in Junior High School - Navisatul Izzah; Sri Wulandari (Tell : Teaching of English Language and Literature Journal, 2023)
The use of Content and Language Integrated Learning (CLIL) has been effective to support learning. However, there are still few teachers that implement CLIL in their classroom. The curriculum and material development were made to support science teacher in implementing CLIL in which the integration of both content and language are highlighted. These were designed to enhance bilingual education program in Sekolah Alam Insan Mulia through CLIL. Specifically, these curriculum and material development were for 7th grade students. Using a curriculum and material development approach with 4Cs Framework for analysis, this study involves the design process of incorporating content with CLIL method intended to promote the learning process with high-quality material and learning methods. The process entailed analysing of the context and the curriculum materials, characterizing students’ opportunities to learn effectively, and assessing students’ learning outcomes. The finding of this study is the product of curriculum and material development using CLIL of a unit entitled interaction with ecosystem. The discussion related the implementation of assessment in CLIL and classroom language use is also presented in this article   Keywords: CLIL, Curriculum and Material Development, Teaching Science